Preparative Separation and Purification of Four Glycosides from Gentianae radix by High-Speed Counter-Current Chromatography and Comparison of Their Anti-NO Production Effects - Bao Chen; Yinghua Peng; Xinhui Wang; Zhiman Li; Yinshi Sun (Molecules, 2017)
Secoiridoid and iridoid glycosides are the main active components of Gentianae radix. In this work, one iridoid and three secoiridoid glycosides from Gentianae radix have been purified by high-speed counter-current chromatography in two runs using different solvent systems. Ethyl acetate–n-butanol–water (2:1:3, v/v/v) was the optimum solvent system to purify ca. 4.36 mg of loganic acid, 3.05 mg of swertiamarin, and 35.66 mg of gentiopicroside with 98.1%, 97.2% and 98.6% purities, respectively, while 31.15 mg of trifloroside with 98.9% purity was separated using hexane–ethyl acetate–methanol–water (1:3:1:3, v/v/v/v). The structures of the glycosides were identified by mass spectrometry and NMR. After separation, the anti-nitric oxide production effects of the compounds on lipopolysaccharide-induced BV-2 murine microglial cells were also evaluated. All of the compounds inhibited the production of nitric oxide in lipopolysaccharide-induced BV-2 cells with high cell viabilities in a concentration-dependent manner, which demonstrated that were able to be used as a nitric oxide inhibitor.